Insecurities of the Workers in the Informal Enterprises: A Study of West Bengal in Comparison to Kerala - Joyita Roy Chowdhury (Research in Applied Economics, 2014)
In the present study we have used the National Sample Survey (NSS) sixty-sixth round (2009-10) unit level data to analyze the various forms of insecurity faced by the workers in the informal sector enterprises of West Bengal and Kerala. The methodological framework of seven forms of insecurities developed by Standing (1999, 2008) is used in the present study. Given the fact that both West Bengal and Kerala are pro-labour states, we try to investigate the differences in the status of the informal workers within the framework of seven forms of insecurities. In a few cases observations from all-India data are added to the entire analysis of comparison between the two states. The analysis finds out that the workers in the informal enterprises irrespective of which state they belong to do not enjoy any employment security (written job contract) and work security (paid leave or social security benefits). In a few cases the observations obtained in Kerala differ from that of West Bengal particularly with respect to skill security. A large number of casual workers in West Bengal are illiterates which have also reduced their access towards obtaining vocational training. The lack of training increases the risk of getting insecure jobs. Another important aspect of vulnerability of the workers is the social groups to which they belong. With respect to income security the condition of the informal workers in West Bengal are worsened as well as they have low collective strength which further accentuates the work related insecurities.